RELATIONSHIP BETWEEN BLOOD GLUCOSE LEVELS AND ENTEROCOCCUS CECORUM FOUND IN KINKY BACK DISEASE IN CHICKENS - K. Özkan (Journal of Animal and Plant Sciences, 2022)
Kinky back (KB) disease in chickens causes significant economic loss in the commercial poultry industries. The aim of the present study was to determine blood glucose levels in broilers with KB disease and the bacterial agents that affect their organs. The glucose levels were measured and Enterococcus cecorum infections were investigated in animals with KB disease. The sixth thoracic vertebrae (T6) and liver samples were taken from 42-d-old Cobb 500 broilers with KB disease from farms located within various geographical areas of Turkey. Ten broilers were selected from each of 10 flocks that showed clinical signs of KB disease (n = 100). Blood samples were taken from the animals in both the control (n = 10) and experimental groups (n = 100) to assess their blood glucose levels. Organ samples were taken from the animals and analyzed using microbiological matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. One-way analysis of variance was used to determine whether there were any statistically significant differences between the means of the control and experimental groups. The bacteriological analyses of the liver and T6 showed that the E. cecorum level significantly increased in the experimental group, which was positively correlated with the increasing glucose levels. Enterococcus cecorum is one of the most important factors causing KB disease, and the most effective method by which to prevent KB disease is a strong biosecurity program inside the poultry houses.
Keywords: Kinky back; Enterococcus cecorum; broiler; glucose; flock